Reproducibility of Accelerometer-Assessed Physical Activity and Sedentary Time - Keadle, Sarah Kozey (Am J Prev Med, 2017)
INTRODUCTION: Accelerometers are used increasingly in large epidemiologic studies, but most studies are restricted to a single, 7-day accelerometer monitoring period given logistic and cost constraints. It is unknown how well a 7-day accelerometer monitoring period estimates longer-term patterns of behavior, which is critical for interpreting, and potentially improving, disease risk estimates in etiologic studies. METHODS: A subset of participants from the Women’s Health Study (N=209; mean age, 70.6 [SD=5.7] years) completed at least two 7-day accelerometer administrations (ActiGraph GT3X+) within a period of 2–3 years. Monitor output was translated into total counts, steps, and time spent in sedentary, light-intensity, and moderate to vigorous–intensity activity (MVPA) and bouted-MVPA (i.e., 10-minute bouts). For each metric, intra-class correlations (ICCs) and 95% CIs were calculated using linear-mixed models and adjusted for wear time, age, BMI, and season. The data were collected in 2011–2015 and analyzed in 2015–2016. RESULTS: The ICCs ranged from 0.67 (95% CI=0.60, 0.73) for bouted-MVPA to 0.82 (95% CI=0.77, 0.85) for total daily counts and were similar across age, BMI, and for less and more active women. For all metrics, classification accuracy within 1 quartile was >90%. CONCLUSIONS: These data provide reassurance that a 7-day accelerometer-assessment protocol provides a reproducible (and practical) measure of physical activity and sedentary time. However, ICCs varied by metric; therefore, future prospective studies of chronic diseases might benefit from existing methods to adjust risk estimates for within-person variability in activity to get a better estimate of the true strength of association.